2021
DOI: 10.1109/access.2021.3065243
|View full text |Cite
|
Sign up to set email alerts
|

Web Browser Privacy: What Do Browsers Say When They Phone Home?

Abstract: We measure the data sent to their back-end servers by five browsers: Google Chrome, Mozilla Firefox, Apple Safari, Brave Browser and Microsoft Edge, during normal web browsing on both desktop and mobile devices. Our aim is to assess the privacy risks associated with this data exchange between a browser and its back-end servers. With regard to shared services, all of the browsers make use of a safe browsing service to mitigate phishing attacks and our measurements indicate that this raises few privacy concerns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Due to the prevalence of ads and analytics scripts that harvest users' information [86], many advertisement and tracker blocking tools have been developed to protect user privacy. Of these tools, the Brave browser has stood out to be one of the best browsers for user privacy on the Clearnet to date [56].…”
Section: Fingerprinting Under Ad Blockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the prevalence of ads and analytics scripts that harvest users' information [86], many advertisement and tracker blocking tools have been developed to protect user privacy. Of these tools, the Brave browser has stood out to be one of the best browsers for user privacy on the Clearnet to date [56].…”
Section: Fingerprinting Under Ad Blockingmentioning
confidence: 99%
“…Therefore, it is straightforward for the adversary to set up an environment that is similar to that of the victim. Specifically, the availability of several OS and device fingerprinting tools based on the different implementations of the TCP/IP stack [16,93], together with well-known "home-phoning" traffic of different web browsers [56], can assist the adversary in fil-tering background noise and resembling a similar browsing environment with the victim.…”
Section: Limitationsmentioning
confidence: 99%
“…It is out of scope to study this issue in detail here, but recall Leith's study of the telemetry communications of six major browsers-Chrome, Firefox, Safari, Brave, Edge and Yandex-by Leith [112]. Leith observed that the identifiers persist over four different timespans: (i) ephemeral identifiers; (ii) session identifiers, reset on browser restart; (iii) browser instance identifiers set on installation, and (iv) device identifiers [112]. Brave uses only ephemeral identifiers; Chrome, Firefox, and Safari use session and browser instance; Yandex uses device identifiers [112].…”
Section: Identifying Device Activitymentioning
confidence: 99%
“…Leith observed that the identifiers persist over four different timespans: (i) ephemeral identifiers; (ii) session identifiers, reset on browser restart; (iii) browser instance identifiers set on installation, and (iv) device identifiers [112]. Brave uses only ephemeral identifiers; Chrome, Firefox, and Safari use session and browser instance; Yandex uses device identifiers [112]. Leith did not give Edge or Yandex a clean bill of health.…”
Section: Identifying Device Activitymentioning
confidence: 99%
“…Additionally, there are situations where adversaries try to exploit the private mode of the web browsers to cover their tracks. Some studies investigated the security of their transmitted information [6], and there are studies that focused on the private mode of particular web browsers [7] or investigated a web browser vendor's claims [8]. As observed in Section 2.2, four prevalent web browsers were chosen for this investigation and analysis.…”
Section: Introductionmentioning
confidence: 99%